Bimetallic PtSn catalyst for the selective hydrogenation of furfural to furfuryl alcohol in liquid phase - Merlo, Andrea Beatriz (2009)
Bimetallic PtSn catalysts, containing different amounts of tin, were obtained by means of controlled surface reactions and used in the liquid-phase hydrogenation of furfural. All the studied systems allowed to obtain fufuryl alcohol with high selectivity (96-98%). A minor product was detected when alcoholic solvent were employed, coming from the reaction between furfuryl alcohol and the solvent. Nonalcoholic and non-polar solvents caused a drastic activity decrease.When used in consecutive hydrogenation reactions, the bimetallic catalysts showed a certain deactivation (25% between the first and third cycle), but still they were very selective to furfuryl alcohol. The most efficient system was the catalyst with the lowest tin content (PtSn0.3).